2010
DOI: 10.1103/physrevb.81.155322
|View full text |Cite
|
Sign up to set email alerts
|

Interference of magneto-intersubband and phonon-induced resistance oscillations in single GaAs quantum wells with two populated subbands

Abstract: Low-temperature electron magnetotransport in single GaAs quantum wells with two populated subbands is studied at large filling factors. Magneto-inter-subband (MIS) and acoustic-phonon induced oscillations of the dissipative resistance are found to be coexisting but interfering substantially with each other. The experiments show that amplitude of the MIS-oscillations enhances significantly by phonons, indicating "constructive interference" between the phonon scattering and the intersubband electron transitions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…To analyze the spectrum the obtained eigenvalues of the Hamiltonian are numerated in ascending order using positive integer index l=1,2.... Eqs. (8,9,10) yield the electron spectrum obtained in a rigid electrostatic potential V (z) that provides a good agreement with experimental data. We relate this agreement with a large gap ∆ 12 between subbands indicating strong electrostatic potential V (z) in the system.…”
Section: B Effect Of In-plane Magnetic Fieldsupporting
confidence: 75%
See 2 more Smart Citations
“…To analyze the spectrum the obtained eigenvalues of the Hamiltonian are numerated in ascending order using positive integer index l=1,2.... Eqs. (8,9,10) yield the electron spectrum obtained in a rigid electrostatic potential V (z) that provides a good agreement with experimental data. We relate this agreement with a large gap ∆ 12 between subbands indicating strong electrostatic potential V (z) in the system.…”
Section: B Effect Of In-plane Magnetic Fieldsupporting
confidence: 75%
“…This coupling in due to the Lorentz force and is described by the off-diagonal matrix T mn in Eq. (10). Figure 4 indicates that the application of in-plane magnetic field increases the interval between consecutive intersections of a Landau level, which is the major effect leading to the increase of MISO period.…”
Section: Miso In Tilted Magnetic Fieldmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to other low-field transport phenomena, such as microwave-induced and Hall fieldinduced [35][36][37][38][39][40][41] resistance oscillations, zero resistance [42][43][44][45][46][47][48][49][50][51][52][53][54] and zero differential resistance [55][56][57] states, PIRO have not received much attention until recently [58][59][60][61][62][63][64][65][66] and several unsolved issues remain.…”
mentioning
confidence: 99%
“…12 have shown that in their experiment the temperature dependence originated from electron-electron interactions modifying the single particle lifetime [15,16]. The same mechanism was later confirmed in studies of the temperature dependence of other related phenomena [17][18][19][20].…”
mentioning
confidence: 83%